Comparative Perspectives on Teaching Foreign Students in Law: Pedagogical, Substantive, Logistical and Conceptual Challenges - Colin Picker; Lucas Lixinski; Alex Steel; Dominic Fitzsimmons (Legal Education Review)
Legal Education has become a global business. Law schools, like the universities in which they sit, increasingly compete for fee-paying foreign or international students. In line with its global approach, this paper discusses the major issues faced by foreign law students from all parts of the world when they go to study in a foreign jurisdiction, either for an initial or postgraduate law degree – by coursework or research. We particularly focus, though not exclusively, on the challenges of students moving to study in English-language jurisdictions. The issues are nuanced and complex, and many law schools and faculty members may be unaware of their overlapping nature. While there is a large and burgeoning literature on the foreign student experience generally, there is little research into foreign students in law, and research that recognises that the factors can vary from country to country. This paper does not report on any new research. Instead it highlights a range of issues that arise from the general literature and from the perspective of teaching and administrative staff, and the authors’ experiences. We suggest that these issues warrant detailed examination in later studies and should be part of any law school’s consideration of how best to support international students.The paper consequently focuses on the issues faced by law school teaching and administrative staff as well as the issues raised for domestic law students as a consequence of the presence and needs of foreign law students. The issues include: the substantive curriculum; logistics & administration; language; pedagogy; and psychological and emotional concerns. Finally, a few examples of approaches and solutions are presented as an indication of possible responses and areas of further research.